2018
DOI: 10.1016/j.comnet.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Online machine learning algorithms to predict link quality in community wireless mesh networks

Abstract: Accurate link quality predictions are key in community wireless mesh networks (CWMNs) to improve the performance of routing protocols. Unlike other techniques, online machine learning algorithms can be used to build link quality predictors that are adaptive without requiring a predeployment effort. However, the use of these algorithms to make link quality predictions in a CWMN has not been previously explored. This paper analyses the performance of 4 well-known online machine learning algorithms for link quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 30 publications
4
56
0
Order By: Relevance
“…Moreover, the work also presents an optimized prediction method that considers the knowledge about the expected LQ values (saturation). Bote-Lorenzo et al [23] identified some limitations and problems of predictive models generated using batch machine learning algorithms in [48]: they cannot be updated once their training has been completed; they impose a predeployment effort (a set of quality samples must be collected in each link before building the corresponding prediction models); and predictions are not available until the observation period is over (which might take a long time). To address these problems, they propose a new hybrid online algorithm for LQ prediction.…”
Section: Link and End-to-end Quality Prediction In Heterogeneous Netwmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the work also presents an optimized prediction method that considers the knowledge about the expected LQ values (saturation). Bote-Lorenzo et al [23] identified some limitations and problems of predictive models generated using batch machine learning algorithms in [48]: they cannot be updated once their training has been completed; they impose a predeployment effort (a set of quality samples must be collected in each link before building the corresponding prediction models); and predictions are not available until the observation period is over (which might take a long time). To address these problems, they propose a new hybrid online algorithm for LQ prediction.…”
Section: Link and End-to-end Quality Prediction In Heterogeneous Netwmentioning
confidence: 99%
“…The evaluation of the proposed algorithm shows that it can achieve a high accuracy while generating a low computational load. The analysis performed by Bote-Lorenzo et al [23] includes a comparison with a baseline (ETX last value). The best overall performance is achieved by both the hybrid online algorithm and the SVM batch algorithm, which outperforms the baseline performance.…”
Section: Link and End-to-end Quality Prediction In Heterogeneous Netwmentioning
confidence: 99%
“…This contributes to maximize the message delivery rate and minimize traffic congestion at both levels (i.e., LQ and EtEQ) with a small average mean absolute error. Additionally, Bote-Lorenzo et al [23] identified several problems and limitations of the predictive models used in [20], through the use of batch machine learning algorithms. Similarly, Lowrance and Lauf [24] provide an exhaustive study of the existing prediction methods to estimate link quality, considering online learning algorithms that increasingly update the network model.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of predictors increases the complexity of the routing protocols, because of the additional hardware and software required to make and validate predictions. Moreover, penalty mechanisms are usually introduced to the system when there is a high rate of mispredictions, which negatively affect the performance of these protocols.Prediction mechanisms have been embedded in routing protocols to foresee several aspects of a network, such as nodes mobility [13], reliability of its topology [14,15] and quality of links and end-to-end paths [16][17][18][19][20][21][22][23][24]. These mechanisms have also been used to reach particular communication…”
mentioning
confidence: 99%
“…Their approach would require decomposing measurements of the SINR into a time-varying component and a non-stationary random part. The authors in [48] proposed a hybrid online machine learning algorithm to estimate the quality of candidate links. Their approach combines current samples of link quality with baseline samples previously learned from past samples.…”
mentioning
confidence: 99%